Enhanced photocatalytic activity of ZnO/g-C3N4 nanofibers constituting carbonaceous species under simulated sunlight for organic dye removal. Issue 18 (15th September 2021) - Naseri, Amene; Samadi, Morasae; Pourjavadi, Ali; Ramakrishna, Seeram; Moshfegh, Alireza Z.
Abstract: Semiconductor-based photocatalysis is an efficient approach for degradation of organic pollutants. In this context, ZnO/g-C3 N4 composite nanofibers containing carbonaceous species with different concentrations of g-C3 N4 nanosheets (x = 0.25, 0.5, 1, 2, 10 wt%) noted as ZnO/carbon/(x wt%) g-C3 N4 are prepared by electrospinning technique. For preparation of the composite nanofibers, bulk g-C3 N4 is exfoliated to nanosheets, and then it is mixed with polyvinyl alcohol and appropriate zinc acetate content followed by electrospinning process. Thermal annealing of the as spun zinc acetate/poly(vinyl alcohol)/g-C3 N4 nanosheets sample under N2 atmosphere leads to the formation of carbonaceous species (Zn–O–C) on the hexagonal wurtzite structured ZnO nanofibers. Moreover, the oxygen vacancy formed in the ZnO structure is verified by X-ray photoelectron spectroscopy (XPS) and electron spin resonance (ESR) techniques. The prepared ZnO/carbon/(0.25 wt%) g-C3 N4 nanofibers demonstrated the highest photocatalytic degradation rate towards methylene blue (MB) at about 2.5 times (with degradation efficiency of 91.8% after 2 h) higher than the ZnO/carbon under similar conditions. To understand the reason behind the improved photocatalytic activity of ZnO/carbon/g-C3 N4 composite nanofibers a mechanism of electron-hole generation, separation and transformation are suggested and a Z-scheme charge transfer approach is proposed. Graphical abstract: Image 1